Design of All Digital Phase Locked Loop for Wireless Applications - R, Swetha; Manjula, J; Ruhan bevi, A (International Journal of Engineering and Technology, 2018)
This paper presents a design of All Digital Phase Locked Loop (ADPLL) for wireless applications. It is designed using master and slave Dflipflop for linear phase detector, counter based loop filter and ring oscillator based Digital controlled oscillator(DCO). The programmable divider is used in the feed-back loop which is used has a frequency synthesizer for wireless applications. It is implemented in 180nm CMOS technology in Cadence EDA tool. The proposed ADPLL has locking period of 50ps and the operating frequency range of 4.7GHz and power consumption of 26mW. Â